Molecular Investigation of Enterococcal Surface protein (esp)gene of Enterococcus faecalis isolated from endodontic patients - A. Mustafa, Eman; M. AL-Rawi, Amera (Medicinski časopis, 2024)
Enterococci are generally considered transient components of oral bacteria that may be a reason for several oral and systemic infections, particularly, those related to dental root canal infections. Aims: The purpose of the current study was to examine the occurrence of Enterococcal Surface protein esp in Enerococcus faecalis which is isolated from infected root canals. Forty samples were collected from endodontic patients who attended the Conservative Treatment Department in the College of Dentistry/Mosul University/Dental Teaching Hospital. Materials and Methods: All samples were examined traditionally by using HiCrom TM Enterococcus faecium Agar base medium and biochemical tests. 16srRNA sequencing was performed to confirm their identity by using the polymerase chain reaction technique. Then all Enterococcus faecalis isolates were examined for the existence of esp gene coding for enterococcal surface protein by using PCR assay. Results: From 40 clinical samples that were obtained, 31 isolates were recognized as E. faecalis by traditional methods, unexpectedly other non-enterococci genera were also grown on HiCrom TM Enterococcus faecium Agar base medium. The PCR products for the sequence-specific primers obtained from the full-length of 16S rRNA gene sequence which belongs to E. faecalis and the PCR products for specific primer of esp genes created bands at the position of 138bp and 932 bp on the agarose gel respectively. This gene which is correlating with the aggregation of this bacteria on the canal walls was detected in high proportion (91%) from the isolates. Conclusions: PCR assay provides an accurate, rapid and more sensitive detection of E. faecalis. A positive correlation has been found between esp gene and enterococcal infections in root canals.
Keywords: Enterococcus faecium; Enterococcal Surface Protein esp gene; Root canals; Polymerase chain reaction assay